PENGEMBANGAN E-LKPD BERBASIS SEJARAH LOKAL PADA PEMBELAJARAN SEJARAH KELAS XI DI SMA NEGERI 1 KATEMAN KABUPATEN INDRAGIRI HILIR - Febriani, Febriani; Ahmal, Ahmal; Asril, Asril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to develop a local history-based worksheet product that can be used in learning the history of the national movement material and to test its feasibility. The research method used is the ADDIE Research and Development Model, namely analysis, design, development, implementation and evaluation. The sample in this study were 27 students of grade XI of SMA Negeri 1 Kateman, Indragiri Hilir Regency. Data collection techniques used in this study were observation, interviews and questionnaires. Data analysis techniques were carried out by processing validator and user response data using a rating scale with a scale of 4, then converted into qualitative data.